Therapeutic efficacy of stem cells (DPSCs, EPCs and HSCs) with TPO-combined treatment for dengue virus infection in mice - Priya, Sivan Padma (2018)
The debilitating diseases are continuously threatening the humankind and raising the economic burden every year. Dengue is one of the highly extending viral infections spreading beyond the endemic borders. Dengue virus (DENV) infects 200 million people per year and disables 3.6 billion people approximately and the recounted threat to public never decline in spite of advances in medical science. Current treatment modalities are principally limited to symptomatic relief yet, accompanies the bitter side of the side effects, intolerance, and drug interaction especially for the patients with co-morbidities or with confusing co-infections. The majority of their pathogenesis has not been detailed. DENV infections effects are principally reported as dysregulated immune responses targeting all major organs. The DENV infection has been reported to target tissues of the blood vessels, liver and bone marrow manifesting with extensive haemorrhages, reduced platelet count, and finally leading to the fatal end in selected individuals. The regenerative medicine has evolved with more promising results with stem cells therapy (SCT). The SCT can be defined as delivering or transplanting primitive cells of the damaged organ or tissue to replace and to augment roles of the injured cells. There were few reports regarding SCT for infections like human immunodeficiency virus and for endotoxin-induced sepsis. The paramount of research on the ability of stem cells with immunomodulatory and antiapoptotic activities have strengthened the idea of novel therapeutic approaches. The principal aim of this study is to investigate the therapeutic ability of dental pulp stem cells (DPSCs) from human cell line along with endothelial progenitor cells (EPCs) of mouse and haematopoietic stem cells (HSCs) of mouse to repair and regenerate the damages induced by DENV2 infection. There were 72 male BALB/c mice brought at the age of eight weeks and were grouped into three as control, infected and not treated with stem cells (Non-SCT), and infected and stem cells treated (SCT). The control was injected with eagle minimum essential media (EMEM) and phosphate buffer saline (PBS). The Non-SCT group mice were infected with DENV2; SCT group were infected with DENV2 and treated with DPSCs, EPCs, and HSCs with a growth factor thrombopoitin. Both the Non-SCT and SCT group were injected intraperitoneally (IP) with DENV2 for consecutive two days. The mice were sacrificed at 5, 10, 15, and 21st day of post-infection by terminal anaesthesia and blood was collected by cardiac puncture to perform haematological and biochemical analysis and the tissues were preserved for histopathological analysis. The Non-SCT group exhibited the marked reduction in platelets, alterations in the liver enzymes and severe pathological damages in the liver and blood vessels. The SCT group exhibited a lesser degree of involvement throughout the experiment and evidenced better recovery by the 21st day. The therapy has aided the recovery and regeneration of the important altered manifestation of dengue such as recovered platelet count, reduced cellular damages, reduced apoptosis, reduced viral load by the end of the 21st day of the experiment. The changes were more significant after the 15th day when the recovering body system suffers from the loss of cells due to extensive viral induced damages which were controlled in SCT group. The finding can conclude the efficacy of the stem cell combination treatment in aiding the alleviation of the dengue induced damages.